Poor Nurses’ Work Environment Increases Quiet Quitting and Reduces Work Engagement: A Cross-Sectional Study in Greece - Ioannis Moisoglou; Aglaia Katsiroumpa; Aggeliki Katsapi; Olympia Konstantakopoulou; Petros Galanis (Nursing Reports)
Background/Objectives: The nursing work environment, encompassing accessible resources and established processes, might affect nurses’ professional behavior. Our aim was to examine the effect of nurses’ work environments on quiet quitting and work engagement among nurses. Methods: We performed a cross-sectional study with nurses in Greece. We used the “Practice Environment Scale-5” to measure nurses’ work environments, the “Quiet Quitting Scale” to measure quiet quitting, and the “Utrecht Work Engagement Scale-3” to measure work engagement among nurses. We developed multivariable regression models adjusted for gender, age, understaffed wards, shift work, and work experience. Results: The study population included 425 nurses. The mean age of the nurses was 41.1 years. After controlling for confounders, we found that lower nurse participation in hospital affairs, less collegial nurse–physician relationships, worse nursing foundations for quality of care, and lower levels of nurse manager ability, leadership, and support were associated with higher levels of quiet quitting among nurses. Moreover, our multivariable analysis identified a positive association between nurse manager ability, leadership, and support, collegial nurse–physician relationships, nursing foundations for quality of care, and work engagement among nurses. Conclusions: Our findings highlight the poor work environment, elevated levels of quiet quitting, and moderate work engagement among nurses. Moreover, we found that a poor nurses’ work environment was associated with higher levels of quiet quitting. Moreover, our findings showed that nurses’ work environments had a positive impact on work engagement. The ongoing endeavor to enhance all aspects of nurses’ working conditions by healthcare organization administrations is essential for optimizing nurses’ performance, facilitating organizational operations, and ensuring service quality.